Floating photovoltaic pilot project at the Oostvoornse lake: Assessment of the water quality effects of three different system designs - Vincent Bax; Wietse I. van de Lageweg; Rik Hoosemans; Bas van den Berg (Energy Reports, 2023)
Floating photovoltaics (FPV) is emerging as a promising renewable energy technology which enables the production of electricity on surface waters. While this technology could potentially make an important contribution to the energy transition, the current uncertainty about the water quality effects of FPV deployment poses a major barrier to FPV project development and implementation. In this study, we investigated the water quality effects of three distinctive FPV system designs, implemented as part of a 1-year pilot project at the Oostvoornse lake, the Netherlands. A water quality monitoring campaign was set up to monitor on a continuous basis a set of key water quality parameters, including light intensity, water temperature and dissolved oxygen concentration. The measurements were conducted below each of the three FPV systems and contrasted with reference measurements at open water adjacent to the systems. Our monitoring results show that of the water quality parameters considered, the impact of the FPV systems on light intensity was found to be most pronounced, with a light reduction between 73% and 100% relative to the reference measurements. We found limited evidence to corroborate that the FPV systems induced changes to the water temperature and dissolved oxygen concentration. However, it must be noted that this study took place under highly specific conditions due the limited size of the FPV pilot systems and the brackish water of the Oostvoornse lake. This means that the water quality effects reported here may not be representative for a larger scale application of the FPV designs, and may not be one-on-one transferable to other, non-brackish project locations elsewhere.